The Cyclic Quadrangle in the Isotropic Plane - Volenec, V.; Beban-Brkić, J.; Šimć, M. (Sarajevo Journal of Mathematics, 2024)
In [15], [2] we focused on the geometry of the non-tangential quadrilateral and in [3], [14] we turned our attention to the non-cyclic quadrangle in the isotropic plane. This paper gives some of the results concerning the geometry of a cyclic quadrangle in the isotropic plane. A cyclic quadrangle is called standard if a circle with the equation y = x 2 is circumscribed to it. In order to prove geometric facts for each cyclic quadrangle, it is sufficient to give a proof for the standard quadrangle. Diagonal points and the diagonal triangle of the cyclic quadrangle are introduced. Some properties of the cyclic quadrangle are given where most of them are related to its diagonal triangle. 2000 Mathematics Subject Classification. 51N25